INFLUENCE OF CENTRAL GOVERNMENT TRANSFER FUNDS AND REVENUE REGIONAL ORIGINS ON GOVERNMENT CAPITAL EXPENDITURE DISTRICT OF WEST SULAWESI PROVINCE - Amina, Nur; Nirwana, Nirwana; Darmawati, Darmawati (Jurnal Akuntansi Bisnis, 2025)
Background:  Capital expenditure is expected to be an allocation of regional costs incurred to allocate resources fairly and appropriately without discrimination, so that the community can enjoy special public services.Objective: The purpose of this essay is to understand how the transfer of Central government and the transfer of Native to the Region affect the modalities of Local government in the Barat Province.Research Methods: This study employs a quantitative approach using second-order data. West Sulawesi Provisional Budget Realization Report is the population in this study. This study's sample is the Realization of West Sulawesi Province Budget for the years 2017–2021. Using the SPSS software, the analysis includes descriptive statistics, classic assumptions, linear multiple regression, test t, test F, and coefficient of determination.Research Results: The results show that the General Allocation Fund and Original Regional Revenue influence capital expenditure, the Special Allocation Fund and Profit-Sharing Fund have no effect on capital expenditure. Simultaneously, General Allocation Funds, Special Allocation Funds, Profit Sharing Funds and Regional Original Income influence the capital expenditure of the regional government of West Sulawesi Province.Originality/Novelty of Research: This research can contribute to the literature with additional information regarding the importance of Central to Regional Government Transfers on Capital Expenditures for Regional Governments and for the Regional Government of West Sulawesi Province.